Ecosystem carbon storage does not vary with mean annual temperature in Hawaiian tropical montane wet forests. (19th June 2014) - Selmants, Paul C.; Litton, Creighton M.; Giardina, Christian P.; Asner, Gregory P.
Abstract Theory and experiment agree that climate warming will increase carbon fluxes between terrestrial ecosystems and the atmosphere. The effect of this increased exchange on terrestrial carbon storage is less predictable, with important implications for potential feedbacks to the climate system. We quantified how increased mean annual temperature (MAT) affects ecosystem carbon storage in above‐ and belowground live biomass and detritus across a well‐constrained 5.2 °C MAT gradient in tropical montane wet forests on the Island of Hawaii. This gradient does not systematically vary in biotic or abiotic factors other than MAT (i.e. dominant vegetation, substrate type and age, soil water balance, and disturbance history), allowing us to isolate the impact of MAT on ecosystem carbon storage. Live biomass carbon did not vary predictably as a function of MAT, while detrital carbon declined by ~14 Mg of carbon ha−1 for each 1 °C rise in temperature – a trend driven entirely by coarse woody debris and litter. The largest detrital pool, soil organic carbon, was the most stable with MAT and averaged 48% of total ecosystem carbon across the MAT gradient. Total ecosystem carbon did not vary significantly with MAT, and the distribution of ecosystem carbon between live biomass and detritus remained relatively constant across the MAT gradient at ~44% and ~56%, respectively. These findings suggest that in the absence of alterations to precipitation or disturbance regimes, the size and distribution of carbon pools in tropical montane wet forests will be less sensitive to rising MAT than predicted by ecosystem models. This article also provides needed detail on how individual carbon pools and ecosystem‐level carbon storage will respond to future warming.